Location, governance, and strategic determinants of japanese manufacturing investment in the united states - Hennart, Jean‐François; Park, Young‐Ryeol (Strategic Management Journal, 1994)
Abstract A firm's decision to manufacture abroad depends on location, governance, and strategic factors. Governance factors are firm‐specific. In spite of this, most empirical studies of foreign direct investment (FDI) have been conducted at the industry level (making it impossible to look at firm‐specific determinants), and only a handful have considered governance, location, and strategic factors simultaneously. This paper is the first large sample study of the determinants of foreign direct investment at the product and firm‐level. It examines the impact of location and governance factors, and of four types of strategic interactions, on a Japanese firm's propensity to manufacture in the U.S. The results support the view that foreign direct investment is explained by location, governance, and strategic variables. Economies of scale and trade barriers encourage Japanese FDI in the U.S. The larger a Japanese firm's R & D expenditures, the greater the probability it will manufacture in the U.S., but this is not the case for advertising expenditures. Some strategic factors are also important: Japanese firms with medium domestic market shares have the highest propensity to invest in the U.S. There is evidence of follow‐the‐leader behavior between firms of rival enterprise groups, but none of ‘exchange‐of‐threat’ between American and Japanese firms. Japanese investors are also attracted by concentrated and high‐growth U.S. industries.